Acessibilidade físico-espacial em hospital público na percepção do usuário com deficiência: estudo de caso nas áreas externas e acessos de hospital universitário em João Pessoa-PB - Silva, Larissa Scarano Pereira Matos da (2014)
About 36% of the northeastern states’ population has some kind of disability that can be motor, hearing, visual, or mental / intellectual in different degrees of difficulty (IBGE, 2010). It is known that these people face daily difficulties, especially in access to health, which is the right of every citizen. It’s known that those people face daily difficulties especially in health access which is their civil law. In this sense architectonics, technological, behavioral or socials obstacles prevent that this civil right has been fulfilled. A public or private affordable place frequently contributes to a more inclusive life and also provides social interaction and personal encouragement to all users. An element that provides the spatial accessibility application is Wayfinding resources, which refers to a set of elements (visual, hearing, tactile, and others one.) that facilitate the spatial orientation of people, especially in a hospital environment where the level of anxiety that disturbs this orientation. Public hospitals ate important centers of medical assistance in various specialties. But the clinic is a functional unit of the establishment of health care for the outpatient care for diagnosis and treatment. The population that frequents these establishments is wide, including physicians, employees from different sectors, visitors, providers, caregivers and patients, who are usually the mostly debilitated. This study has as a purpose to evaluate the physical-spatial accessibility through user’s perception with disabilities. For this reason a case study was conducted in the outpatient Lauro Wanderley University Hospital-UFPB. The methodology was divided into five stages: bibliographical and documentary research, recognition and characterization of the area, assessment of user’s perspective and finally, analysis and systematization of the results. It was possible to identify the problems encountered by users and map the most critical points but especially to understand how patients are oriented in environments. Finally, adjustments are proposed for improvements of space and wayfinding.